Folleto de juegos linguísticos para implicar a los estudiantes de las clases de Francés - Monteagudo González, Carmen Lilian (Universidad Central "Marta Abreu" de Las Villas. Facultad de Lengua Extranjeras.Departamento de Lenguas Extranjeras, 2020)
The major paper entittled “A linguistic game booklet to engage sixth graders in French speaking lessons” was implemented in a group of students (members of the Special Interest Group on French language) from "Zeneido Costa LLerena" Elementary School in Santa Clara, with the objective of having them to be more involved in the French speaking lessons as they were interested in learning to communicate in this second foreign language. Their interest of having more attention and involvement during the lessons was known through the administration of some empirical methods such as participant observations, a survey and a pedagogical test. The booklet has eight games that were a result of a building up process. All the games introduced in the teaching learning process functioned well due to their role in motivating and in mobilizing the activity in the multiple ways of organizing the teaching and learning process. The results showed the students´ motivation in learning French, their energy in the lessons and their improvement in pronunciation, vocabulary and gramma
Alinguistic game booklet to engage sixth graders in French espeaking lessons
Keywords: Educación; Educación Superior; Didáctica del Inglés; Enseñanza de la Lenguas Extranjeras; Lenguas Extranjeras